Effect of spironolactone on the risks of mortality and hospitalization for heart failure in pre-dialysis advanced chronic kidney disease: A nationwide population-based study. (1st July 2017) - Tseng, Wei-Cheng; Liu, Jia-Sin; Hung, Szu-Chun; Kuo, Ko-Lin; Chen, Yu-Hsin; Tarng, Der-Cherng; Hsu, Chih-Cheng
Abstract: Background: Spironolactone has been shown to reduce cardiovascular death in patients with mild-to-moderate chronic kidney disease (CKD), but its risks and benefits in advanced CKD remain unsettled. We aimed to assess whether spironolactone reduces cardiovascular mortality and morbidity in pre-dialysis stage 5 CKD patients. Methods: Using Taiwan's National Health Insurance Research Database from January 2000 to June 2009, we enrolled 27, 213 pre-dialysis stage 5 CKD adult patients, in whom 1363 patients were treated with spironolactone (user) and 25, 850 were not (nonuser). Outcomes were all-cause mortality, hospitalization for heart failure (HHF) and major adverse cardiac event (MACE, the composite of acute myocardial infarction and ischemic stroke). Patients were followed up till December 31, 2009. Results: Over 85, 758 person-years of follow-up, spironolactone users had higher incidence for all-cause mortality (24.7/100 person-years vs. 10.6/100 person-years), infection-related death (4.4/100 person-years vs. 1.7/100 person-years) and HHF (4.0/100 person-years vs. 1.4/100 person-years). Multivariable Cox hazards model showed that spironolactone users were associated with higher risks of all-cause mortality (adjusted hazard ratio [aHR] 1.35, 95% confidence interval [CI] 1.24–1.46), infection-related death (aHR 1.42, CI 1.16–1.73) and HHF (aHR 1.35, CI 1.08–1.67) as compared to nonusers. The risks for cardiovascular mortality, MACE and hyperkalemia-associated hospitalization were similar between two groups. After matching users and nonusers (1:3 ratio) by propensity scores, the results were consistent in matched cohort and across subgroups. Conclusions: Spironolactone may be associated with higher risks for all-cause and infection-related mortality and HHF in pre-dialysis stage 5 CKD patients. Spironolactone should be used with caution in advanced CKD patients. Highlights: Spironolactone is associated with higher mortality and hospitalization for heart failure in anemic, hypertensive, advanced CKD patients. Cardiovascular mortality, MACE and hyperkalemia-associated hospitalization were similar between spironolactone users and non-users. Clinicians should use spironolactone with caution in these pre-dialysis stage 5 CKD patients.